Vasyl Sukhomlynsky on Psychological and Educational Characteristics of Student’s Personality - MIHNO, Oleksandr (Journal of Education, Technology and Computer Science, 2013)
The article highlights the evolution of Vasyl Sukhomlynsky’s views on the research of student’s personality; in the article principal student’s psychological and educational characteristics have been described.